Sorting device for waste lithium-ion power battery fragments - MA CHENG; YIN KANGJIAN; XIA XIONGWEI; XUE XIN (2016)
The invention discloses a sorting device for waste lithium-ion power battery fragments. The sorting device comprises high-pressure water nozzles, a vibrating screen, an inclined stirring paddle, a diaphragm shell fragment discharging port, a current collector fragment discharging port, an electrode material outlet, an electrode material storage tank, a current collector outputting belt, a current collector fragment storage tank, a diaphragm shell outputting belt, a diaphragm shell fragment storage tank and a wet rotary drum. By means of the sorting device, the purpose of sorting various materials in waste lithium-ion power battery fragments can be achieved, the harm of waste lithium-ion power batteries to the ecological environment can be reduced, the recycling rate of resources can be increased, and meanwhile the industry cost burden brought by the lithium raw material can be reduced. 本发明公开了种废旧锂离子动力电池碎料分选装置，所述分选装置包括高压水喷头、震动筛网、倾斜式搅拌桨、隔膜外壳碎料出料口、集流体碎料出料口、电极材料出口、电极材料储存罐、集流体输出带、集流体碎料储存罐、隔膜外壳输出带、隔膜外壳碎料储存罐和湿式滚筒。利用该